Advances in oxide semiconductors for surface enhanced Raman scattering. (December 2022) - Du, Xuejian; Liu, Di; An, Keyu; Jiang, Shouzhen; Wei, Zhixian; Wang, Shuangpeng; Ip, Weng Fai; Pan, Hui
Highlights: Oxide semiconductors with unique properties can serve as the robust SERS substrates. Recent development on the SERS-active oxide semiconductor nanomaterials was summarized. Dominant enhancement mechanism for the enhanced SERS of oxides was discussed elaborately. Effective strategies for improving the SERS performance of semiconducting oxides were highlighted. Current challenges and future perspectives on oxide-based SERS substrates were outlined. Abstract: Surface enhanced Raman scattering (SERS) has been recognized as a powerful and useful spectroscopic technology with the capability of ultra-high sensitivity for single-molecule detection. Noble metals, such as Au, have been considered as the best substrates for SERS because of their high detection limit. However, their practical application is hindered by high cost, long-term instability, inferior reproducibility, poor biocompatibility and difficult integration with modern electronic devices. Recently, oxide semiconductors have attracted tremendous attention for their applications into SERS as they can perfectly solve the pre-mentioned challenging issues. Furthermore, the oxide semiconductor SERS substrates can realize selective detection and recyclable usage, leading to their powerful integration with the electronic devices. In the review, we shall summarize the recent advances of oxide semiconductor-based SERS substrates, and highlight the effective strategies, including defect engineering, hybridization, structure manipulation, and configuration design, to boost their SERS performance for commercial applications. At the end, current challenges and future perspectives are concisely discussed, aiming at elevating the SERS activity and broadening their practical applications.